Analysing the influence of organisational culture and leadership styles on the implementation of lean manufacturing. Issue 15 (18th November 2021) - Tortorella, Guilherme Luz; Fettermann, Diego; Fogliatto, Flavio S.; Kumar, Maneesh; Jurburg, Daniel
Abstract: This paper aims at identifying the combination of organisational culture profiles and leadership styles that best support companies implementing lean manufacturing practices. For that, 225 leaders from manufacturing companies at various stages of lean implementation were surveyed. The analytical approach clustered respondents and their respective firms according to prevailing organisational culture, leadership style and level of implementation of lean practices, testing for frequency differences among clusters. This study states that organisational culture profiles are related to leadership styles and lean manufacturing implementation level, suggesting different-from-expected effects of this relationship on lean manufacturing implementation. The study bridges a gap in the literature by exploring how the association between organisational culture and leadership styles occurs in companies that are adopting lean practices.